The quadratic formula is given by:
x = (-b ± √(b^2 - 4ac)) / (2a)
In the given equation, a = 4, b = 3, and c = -10. Substituting these values into the quadratic formula, we get:
x = (-(3) ± √((3)^2 - 4(4)(-10))) / (2(4))
Simplifying:
x = (-3 ± √(9 + 160)) / 8
x = (-3 ± √169) / 8
x = (-3 ± 13) / 8
This gives two possible solutions:
x₁ = (-3 + 13) / 8 = 10 / 8 = 1.25
x₂ = (-3 - 13) / 8 = -16 / 8 = -2
Therefore, the solutions to the equation are x = 1.25 and x = -2.
Solve the equation using the quadratic formula.
4 lower x squared plus 3 lower x minus 10 equals 0
(1 point)
1 answer